2015
DOI: 10.1002/nme.5129
|View full text |Cite
|
Sign up to set email alerts
|

Numerical implementation and validation of a consistently homogenized higher order plasticity model

Abstract: Summary A homogenization theory was developed earlier that starts with a meso‐scale gradient plasticity model at the bottom and recovers a macroscopically continuous micromorphic model at the top. Through the scale transition framework, the granular mechanics are smeared consistently over a single grain such that the fine scale properties, microstructural length scale (l), and grain size (L) manifest themselves naturally in the homogenized relations, a point of departure from many continuous higher order theor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 46 publications
(126 reference statements)
0
4
0
Order By: Relevance
“…In this paper, we adopt the homogenization theory that was first developed for gradient plasticity models in Poh et al (2013) and Poh (2013), with its excellent performance demonstrated in Poh and Phan (2016). Here, the theory is reformulated for the translation of intergranular failure mechanisms from meso to macro.…”
Section: Homogenization Strategymentioning
confidence: 97%
“…In this paper, we adopt the homogenization theory that was first developed for gradient plasticity models in Poh et al (2013) and Poh (2013), with its excellent performance demonstrated in Poh and Phan (2016). Here, the theory is reformulated for the translation of intergranular failure mechanisms from meso to macro.…”
Section: Homogenization Strategymentioning
confidence: 97%
“…Moreover, Poh and Peerlings [59] numerically elucidated that the localization phenomenon that takes place in Bittencourt et al [65] composite unit cell benchmark problem can only be reproduced by DGP. Gurtin [15] theory has also been employed by Poh and co-workers [66,67] through a novel homogenization formulation to describe the behavior of each grain in a polycrystal where grain boundaries are modeled to describe effects of dislocation blockage or transmittal.…”
Section: Dissipative Contributionsmentioning
confidence: 99%
“…Moreover, Poh and Peerlings [28] showed that the localization phenomenon that takes place in Bittencourt et al [29] composite unit cell benchmark problem can only be reproduced by distortion gradient plasticity. Other recent works involve the development of new homogenization formulations [30,31] and finite element schemes [32][33][34]. However, the implications of distortion gradient plasticity on crack tip mechanics remain to be addressed.…”
Section: Introductionmentioning
confidence: 99%